1999
DOI: 10.1080/089583799197212
|View full text |Cite
|
Sign up to set email alerts
|

Acute Biological Effects of Intratracheally Instilled Titanium Dioxide Whiskers Compared With Nonfibrous Titanium Dioxide and Amosite in Rats

Abstract: The dimensions of man-made mineral fiber whiskers are similar to those of some kinds of asbestos. Thus these mineral fibers raise the concern for potential health hazard for workers exposed in the occupational environments. This study was designed to define acute biological effects of intratracheally administered titanium dioxide whiskers (TO1) compared with nonfibrous titanium dioxide (TOP) and UICC amosite (Ams), and their relations to acute lung inflammation in rats. The observed geometric mean length (micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…These observations correlated well with the changes of cellularity in BAL fluid. We previously observed overexpression of eotaxin mRNA concomitant with eosinophils infiltration in the lungs of rats treated with TO1 or UICC amosite (Ishihara et al, 1999). Overexpression of eotaxin mRNA, as well as increased BAL eosinophils, was also observed in this study.…”
Section: Discussionsupporting
confidence: 77%
“…These observations correlated well with the changes of cellularity in BAL fluid. We previously observed overexpression of eotaxin mRNA concomitant with eosinophils infiltration in the lungs of rats treated with TO1 or UICC amosite (Ishihara et al, 1999). Overexpression of eotaxin mRNA, as well as increased BAL eosinophils, was also observed in this study.…”
Section: Discussionsupporting
confidence: 77%
“…Markers of cellular permeability and damage were also augmented at most of the time points both in the amosite and in the high-dose LA groups. Increased protein in BAL fluid, likely due to increased epithelial permeability, was reported previously in rats exposed to amphibole asbestos by inhalation (Petruska et al 1991) and IT instillation (Ishihara et al 1999;Adamis et al 2001). LDH was elevated in both FIGURE 9.…”
Section: Discussionmentioning
confidence: 56%
“…In our study, both lung tissue mRNA and BAL fluid protein levels of TNF-α were elevated at 1 d in animals exposed to the amosite and high-dose LA. Prior studies also reported increases in TNF-α mRNA expression after amosite exposure in rats, but no changes in BAL fluid protein levels (Ishihara et al 1999). Persistently lower levels of BAL fluid IL-1β were observed in the high-dose LA group, while tissue mRNA levels were unchanged over time.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Ishihara et al 21) studied gene expression in lung tissue after intratracheal instillation of mineral fibers in rats. Exposure to fibrous titanium dioxide whiskers or amosite increased in total protein and expression of cytokine-induced neutrophil chemoattractant / growth-regulated gene, but exposure to nonfibrous titanium dioxide did not.…”
Section: Chemokinesmentioning
confidence: 99%